The Role Of The Deli Serdang Traffic Police Unit In Increasing Public Legal Awareness In Traffic In The Jurisdiction Of The Deli Serdang Police - Esron Ginting; T. Riza Zarzani (International Journal of Society and Law, 2024)
The police institution, as a legal entity, plays a critical role in ensuring law enforcement and public order within a community. This study focuses on the role of the Deli Serdang Traffic Police Unit (Satlantas) in increasing public legal awareness in traffic within the jurisdiction of the Deli Serdang Police. Amid rapid modernization, population growth, and escalating motor vehicle usage, traffic issues such as violations and accidents have become prevalent, underscoring the need for effective law enforcement strategies. The research examines the contributions of Satlantas in addressing these challenges, highlighting its efforts in regulation, education, and fostering a culture of traffic order. Furthermore, the study explores the obstacles faced by Satlantas in implementing these initiatives, providing insights into integrated strategies to enhance public compliance with traffic laws.